(untitled) (Conference on English Language Teaching, 2024)
The present study aims to explore English pronunciation and vocabulary acquisition of EFL students in Indonesian secondary schools throuh English films and online games. School learning or often called formal learning needs to be supported by other learnings to get maximum results from the learning. Using a qualitativecase study method, the authors can identifythe stuemts’ interests and abilities in English using an online interview through filling out questionnaires that have been presented by the authors. The results show that most studentshad positive response toward the use of film and online games can foster English pronunciation and vocabulary development. The study provides a contribution in helping students in the learning process to improve English language skillsespecially speaking.